2020
DOI: 10.1016/j.heliyon.2020.e05310
|View full text |Cite
|
Sign up to set email alerts
|

Soil texture and watering impact on pot recovery of soil-stripped oil palm (Elaeis guineensis Jacq.) seedlings

Abstract: The transportation load of oil palm ( Elaeis guineensis Jacq.) seedlings from the nursery to planting sites is a crucial problem facing the extension of smallholder plantations in Cameroon. This load can be considerably reduced by removing soil from the roots, which in turn exposes the plants to water and nutrients stresses. A greenhouse pot experiment was carried out to evaluate the recovery performance of such soil-stripped seedlings as a function of watering frequency and soil texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Andrade et al (2020) [75] observed a better correlation of microporosity with AWC. Thus, soils with a predominance of micropores tend to store more water [76]. On the other hand, in the two deeper soil layers between 0.1 and 0.4 m, in addition to the correlations observed in the surface layer, AWC was also directly correlated with total porosity, PWP, and clay and inversely correlated with bulk density (BD) and sand content.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Andrade et al (2020) [75] observed a better correlation of microporosity with AWC. Thus, soils with a predominance of micropores tend to store more water [76]. On the other hand, in the two deeper soil layers between 0.1 and 0.4 m, in addition to the correlations observed in the surface layer, AWC was also directly correlated with total porosity, PWP, and clay and inversely correlated with bulk density (BD) and sand content.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding soil texture, silt and clay contents are strongly associated with PWP. Anaba et al (2020) [76] observed that the relationship between the physical-hydric attributes could explain this behavior since the finer fractions (silt and clay) of the soil have greater participation in water retention at high potentials due to larger specific surfaces. Other soil attributes, such as BD and particle density (PD), were also related to particle size fractions, mainly associated with sand content.…”
Section: Discussionmentioning
confidence: 99%
“…Soil texture will affect the soil's ability to store and provide plant nutrients (Chakraborty and Mistri, 2015). The clay fraction can attract and hold nutrients Table Copyright © 2023 Universitas Sebelas Maret so that a few nutrients will be lost by water flowing through the soil (Anaba et al, 2020).…”
Section: Physical and Chemical Soil Characteristicsmentioning
confidence: 99%
“…One study used 14 different soil textures and chemical variables on six palm oil plantations to measure the effects on palm oil and the physicochemical properties of soil [64]. Anaba et al [65] mentioned that palm oil physiological and behavioural adaptations to survive were defined as early tenera hybrid seedling stages. Sandy soils with macropores exhibit low resistance to penetration, producing excellent root growth in length and ramification.…”
Section: Factors Affecting Palm Oil Growth and Qualitymentioning
confidence: 99%